Comparison of the 7th Grade Students’ Accomplishments in Skill and Acquisition Based Assessment-Evaluation - Ali Kolomuc; Zafer Karagölge (Journal of Science Learning, 2021)
This study compares the successes of numbers 94 7th grade students in science education with assessment-evaluation questions based on skill and acquisition. Assessment-evaluation achievement tests based on skill and acquisition were developed by researchers towards the measurement of force and acquisitions in friction units taking place in the 7th-grade curriculum. While skill-based questions are being prepared, High School Entrance Exam (HSEE) and international exams such as Programme for International Student Assessment (PISA) were developed due to inspiration from Trends in International Mathematics and Science Study (TIMSS) exam questions and acquisition-based assessment and evaluation questions were taken from pre-exam books. It was found that the reliability coefficient for the traditional test is 0.70 and for the skill-based test is 0.72. At the same time, students’ opinions were taken to detect students' perspectives against skill and acquisition-based questions after application. According to the statistical results gathered from research, the academic achievements of students who are prepared with the same acquisitions and applied with skill and acquisition-based assessment-evaluation questions were analyzed. It was determined that despite the lack in solving skill-based questions, students were successful in acquisition-based assessment-evaluation. The students' average success in the acquisition-based test was 76 out of a hundred, and the average score in the skill-based test was 44. Besides, it can be considered to extend skill-based questions for Turkey to go beyond successes.